A new R package, exsic, to assist taxonomists in creating indices1. (7th June 2013) - Simon, Reinhard; Spooner, David M.
Abstract : Premise of the study: Taxonomists manage large amounts of specimen data. This is usually initiated in spreadsheets and then converted for publication into locality lists and indices to associate collectors and collector numbers from herbarium sheets to identifications ( exsiccatae ). This conversion process is mostly done by hand and is time‐consuming, cumbersome, and error‐prone. Methods and Results: We constructed a tool, 'exsic, ' based on the statistical software R. The exsic function is part of the R package 'exsic' and produces specimen citations and exsiccatae conforming to four related formats. Conclusions: The tool increases speed, efficiency, and accuracy to convert raw spreadsheet tables to publication‐ready content.